Differentiating nanomaghemite and nanomagnetite and discussing their importance in arsenic and lead removal from contaminated effluents: A critical review - Ramos-Guivar J.A. (2021)
The authors thank the Fondo Nacional de Desarrollo Cient?fico, Tecnol?gico y de Inno-vaci?n Tecnol?gica (PROCIENCIA-CONCYTEC), project number: 177-2020-FONDECYT (PROCIEN-CIA), project CLEAN NANOMAGNETIC. The APC was funded by PROCIENCIA. Acknowledgments: Edson C. Passamani is also thankful to FAPES and CNPq for their financial support in the infrastructure of Ufes?s laboratory under his supervision. We finally thank Jean-Marc Greneche for supporting us with the in-field M?ssbauer measurement of NPEDTA samples.